Convert the verbal expression with its equivalent algebraic expression. Use r for any unknowns and simplify your answer. If applicable, put the constant at the beginning of the expression. three-quarters the sum of seven and a number The mathematical equivalent of this phrase is:

Asan yung ipapasagot mo???

[tex]9x^2+5[/tex]

Step-by-step explanation:

Let x represent the unknown number.

We are asked to convert the verbal expression with its equivalent algebraic expression..

Five more than a nine times square of a number.

Square of the number would be [tex]x^2[/tex].

Nine times square of the number would be 9 multiplied by [tex]x^2[/tex] as:

[tex]9x^2[/tex].

Five more than a nine times square of a number would be [tex]9x^2[/tex] plus 5 as:

[tex]9x^2+5[/tex]

Therefore, our required expression would be [tex]9x^2+5[/tex].

T = 42.08 °C

Explanation:

Using the expression,

[tex]\ln \dfrac{k_{1}}{k_{2}} =-\dfrac{E_{a}}{R} \left (\dfrac{1}{T_1}-\dfrac{1}{T_2} \right )[/tex]

Wherem

[tex]k_1\ is\ the\ rate\ constant\ at\ T_1[/tex]

[tex]k_2\ is\ the\ rate\ constant\ at\ T_2[/tex]

[tex]E_a[/tex] is the activation energy

R is Gas constant having value = 8.314 J / K mol

Thus, given that, [tex]E_a[/tex] = 45.6 kJ/mol = 45600 J/mol (As 1 kJ = 1000 J)

[tex]k_2=2\times k_1[/tex]

[tex]k_1=0.0160s^{-1}[/tex]

[tex]T_1=30\ ^0C[/tex]

The conversion of T( °C) to T(K) is shown below:

T(K) = T( °C) + 273.15

So,

T = (30 + 273.15) K = 303.15 K

[tex]T_1=303.15\ K[/tex]

So,

[tex]\ln \dfrac{k_{1}}{2\times k_{1}} =-\dfrac{45600}{8.314} \left (\dfrac{1}{303.15}-\dfrac{1}{T_2} \right )[/tex]

[tex]\ln \dfrac{1}{2} =-\dfrac{45600}{8.314} \left (\dfrac{1}{303.15}-\dfrac{1}{T_2} \right )[/tex]

[tex]8.314\ln \left(2\right)=-45600\left(\frac{1}{303.15}-\frac{1}{T_2}\right)[/tex]

[tex]8.314\ln \left(2\right)=-150.42058+\frac{45600}{T_2}[/tex]

[tex]144.65775 =\frac{45600}{T_2}[/tex]

[tex]T_2=\frac{45600}{144.65775}[/tex]

[tex]T_2=315.23\ K[/tex]

Conversion to °C as:

T(K) = T( °C) + 273.15

So,

315.23 = T( °C) + 273.15

T = 42.08 °C

Question:

Select expression that is mathematically equivalent to

[tex]\frac{x}{y-z} + (a-b)*c[/tex]

a) [tex]x/y - z + (a - b) * c[/tex]

b) [tex]x/(y - z) + (a - b) * c[/tex]

c) [tex]x/y - z + a - b * c[/tex]

d) [tex]x/(y - z) + a - b * c[/tex]

[tex]x/(y - z) + (a - b) * c[/tex]

Step-by-step explanation:

Given

[tex]\frac{x}{y-z} + (a-b)*c[/tex]

Required

Determine its equivalent

Start by writing y - z in bracket;

[tex]\frac{x}{y-z} + (a-b)*c[/tex]

becomes

[tex]\frac{x}{(y-z)} + (a-b)*c[/tex]

When - is used as divide, it is equivalent to /

The given expression can then be rewritten as

[tex]x/(y - z) + (a - b) * c[/tex]

Hence;

[tex]\frac{x}{y-z} + (a-b)*c[/tex] is equivalent to [tex]x/(y - z) + (a - b) * c[/tex]

Explanation:

2t2 is 1 1t1 = 11 11t2

1212t12 = 0 0t2=2 der fo it 2

p - 6

I hope this helps!

y - y1 = m(x- x1)

y - (-5) = 2/3(x -0)

y + 5 = 2/3x

y = 2/3x - 5

10/60

step-by-step explanation:

if you divide 10 by 60 the answer is 0.166666 while if you divide or solve the other problems it equals 0.6

Sum is addition, less than is subtraction, equals is is, division is of and multiplication is per